SPECIFIED 21ST CYBER-BASED LEARNING ACTIVITIES: PERSPECTIVES FROM JHS EFL TEACHERS IN INDONESIAN EFL CONTEXT - Wulandari, Cok Istri Agung Sri; Aryati, Ni Putu Puspita Selly; Permatasari, Ni Putu Intan (Universitas Muhammadiyah Semarang, 2019)
This study aimed at investigating the specified 21st Cyber-based learning activities. The emergence of using specified 21st cyber-based learning activities is due to the integration of digital literacy and the 4Cs. The method of the study is descriptive qualitative study with SWOT data analysis technique. Then, to ensure the validity and reliability of the data analysis, methods triangulation was used to check the consistency of findings generated by different data collection methods. The data were collected through documents analysis, classroom observation, and interview section. The result of the study showed that JHS EFL teachers have different perspectives about the specified 21st cyber-based learning activities due to cultural attributes of Indonesian EFL learners which have society’s perspective behavior of collectivism, reticence and passivity. However, in line with the use of specified 21st century-based learning activities, another result showed that students need EFL learning activities which implementing the subskills of the 4Cs. Additionally, the EFL learning activities should be integrated with the 4Cs both in the cyber-based and classroom-based learning to answer the education challenge in 21st century education.